Hypermethylation of the Nrf2 Promoter Induces Ferroptosis by Inhibiting the Nrf2-GPX4 Axis in COPD - Zhang, Zixiao; Fu, Congli; Liu, Jiaxin; Sai, Xiaoyan; Qin, Chu; Di, Tingting; Yang, Yue; Wu, Yan; Bian, Tao (International journal of chronic obstructive pulmonary disease, 2021)
Nuclear factor E2-related factor 2 (Nrf2) is involved in oxidative stress and lung inflammation and regulates the etiology of chronic obstructive pulmonary disease (COPD). Ferroptosis is characterized by the accumulation of lipid reactive oxygen species (ROS) via ferrous ion-dependent Fenton reactions and is involved in COPD. However, the role of Nrf2 in ferroptosis and its epigenetic regulation in the pathogenesis of COPD remain unclear. Ferroptosis was detected by 4-HNE, MDA, C11BODIPY, DCFH-DA, Peals' staining and CCK-8 assays. qPCR and Western blotting were performed to examine the Nrf2 levels in peripheral lung tissues, primary epithelial cells collected from patients with COPD and subjects with normal pulmonary function (never-smoker [control-NS]; smoker [control-S]), and cigarette smoke extract (CSE)-treated human bronchial epithelial (HBE) cells. ELISA was used to quantify IL-8 and IL-1β levels. Methylation of the Nrf2 promoter was analyzed by bisulfite sequencing and pyrosequencing. Ferroptosis was involved in COPD and glutathione peroxidase 4 (GPX4) expression was downregulated in the COPD group. Reactive oxygen species (ROS), lipid peroxides and MDA were increased, but GPX4 and SOD were exhausted in CSE-treated HBE cells. The production of IL-1β and IL-8 was promoted in HBE cells in response to CSE but could be reversed by the ferroptosis inhibitor fer-1. The Nrf2 level was significantly decreased in the COPD group compared with the control-S and control-NS groups. Increased Nrf2 expression enhanced GPX4 and SOD levels and inhibited ferroptosis and proinflammatory cytokines in the supernatant. Inhibition of GPX4 reversed the effect of Nrf2 overexpression and promoted ferroptosis. Two specific CpG sites within the Nrf2 promoter were hypermethylated in the COPD group. Similarly, CSE-treated HBE cells exhibited hypermethylation of the Nrf2 gene. Nrf2 expression was downregulated in the lungs of COPD patients due to hypermethylation of the Nrf2 promoter, inhibiting Nrf2/GPX4 and ferroptosis, which is related to the initiation and progression of COPD. Targeting Nrf2/GPX4 may inhibit ferroptosis, which could provide strategies to delay or treat COPD.